(untitled) (Ibrahim Medical College Journal, 2014)
Plant materials are considered to be attractive potential sources of alternate agents in the prevention and management of type 2 diabetes mellitus (T2DM). Different parts of Aegle marmelos have been claimed to possess anti-glycemic property. The present study was conducted at Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka, Bangladesh from July 2010 to June 2011 to determine the anti-glycemic effect of A. marmelos unripe fruit pulp in T2DM patients. The experiment was conducted under a crossover design and the effects were analyzed during the 0-21 as well as 28-49 days with 7 days wash out period. The data were then pooled and the baseline versus endpoint values was also compared. The mean fasting blood glucose (FBG) values did not significantly differ between the two groups at any time points. No significant difference between the baseline and end point values regarding FBG. The effect on blood glucose was not significant in any of the analysis. This study did not reveal any antiglycemic effect of A. marmelos fruit pulp in T2DM patients. DOI: http://dx.doi.org/10.3329/imcj.v7i2.20109 Ibrahim Med. Coll. J. 2013; 7(2): 35-37